2016
DOI: 10.1186/s13041-016-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial division inhibitor Mdivi-1 rescues mammalian neurons from anesthetic-induced cytotoxicity

Abstract: BackgroundConcerns have risen regarding the potential side effects of clinical exposure of the pediatric population to inhalational anesthetics, and how they might impact cognitive, learning, and memory functions. However, neither the mechanisms of anesthetic cytotoxicity, nor potential protective strategies, have yet been fully explored. In this study, we examined whether two of the most commonly used inhalational anesthetics, sevoflurane and desflurane, affect neuronal viability and synaptic network assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 35 publications
3
44
3
Order By: Relevance
“…The effects of mdivi-1 are also controversial, especially in terms of its specificity in inhibiting Drp1. Although studies have shown that mdivi-1 inhibits mitochondrial fission, 32,[76][77][78][79][80][81] researchers have also reported that mdivi-1 inhibits complex I of the electron transport chain at concentrations greater than 25 μM. 52 A more recent study showed mdivi-1 is a Drp1 inhibitor that increased complex I, II, and IV enzymatic activities at a concentration of 25 μM.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of mdivi-1 are also controversial, especially in terms of its specificity in inhibiting Drp1. Although studies have shown that mdivi-1 inhibits mitochondrial fission, 32,[76][77][78][79][80][81] researchers have also reported that mdivi-1 inhibits complex I of the electron transport chain at concentrations greater than 25 μM. 52 A more recent study showed mdivi-1 is a Drp1 inhibitor that increased complex I, II, and IV enzymatic activities at a concentration of 25 μM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young rodents exposed to volatile anesthetics including sevoflurane and isoflurane were found to have deficits in long-term memory (Ramage et al, 2013 ). Rat cortical neurons exposed to either sevoflurane or desflurane demonstrated increased cell death, decreased neurite outgrowth and compromised mitochondrial integrity and synaptic function (Xu et al, 2016 ). Studies involving neonatal rodent exposure to intravenous anesthetics such as ketamine and propofol have also described detrimental effects on neuronal survival, dendritic spine density, and memory (Cattano et al, 2008 ; Pesić et al, 2009 ; Briner et al, 2011 ; Huang et al, 2012 ; Yu et al, 2013 ).…”
Section: Clinical Research Related To Anesthetic-induced Neurotoxicitmentioning
confidence: 99%
“…In addition, we systematically evaluate the subcellular impact of modern general anesthetics on neuronal excitability, viability, and connectivity between developing neurons. While many of the findings reviewed here emanate from research conducted on various molluscs, particularly the fresh water snail Lymnaea , these data have nevertheless stood the test of time as it pertains to vertebrates (Xu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 96%
“…While it is logical that the observed decrease in inhibitory synaptic neurotransmission may be due to the observed effects on the mitochondria, other explanations are not excluded by these data. Interestingly, in a recent paper, Xu showed that sevoflurane-induced apoptosis in primary cultured neurons could be prevented using a mitochondrial division inhibitor 98 . At this point, there is strong evidence to suggest that early anesthetic exposure strongly affects mitochondrial structure and function in neurons, and there is emerging evidence that mitochondrial disturbance may be associated with decreased synaptic transmission, a known inducer of apoptosis in developing neurons.…”
Section: Effects On Mitochondriamentioning
confidence: 99%